Peran Mahasiswa dalam Pengabdian Masyarakat untuk Meningkatkan Tri Dharma Perguruan Tinggi di Desa Hulu Kecamatan Pancur Batu - Silitonga, Afrini Yuninda; Septiani, Annisa Tri; Irhamna, Irhamna; Fathurrahman, Fathurrahman; Pasya, Nazwa; Ramadhani, Susan; Diva, Rangga; Sebayang, Khairunnisa; Kusniadi, Adjie Iqthiar; Nabila, Nur’aida; Ananda, Nadya Dwi (VISA: Journal of Vision and Ideas, 2024)
Higher education institutions has a significant contribution in improving the quality of human resources. Community service is one of the pillars of the Higher Education Tri Dharma, alongside education and teaching duties as well as research duties. This is stated in article 24, point 22 of Law No. 20 of 2003. This journal investigates the effectiveness of mutual cooperation activities, elderly gymnastics, and Yasin recitations in improving the implementation of the Higher Education Tri Dharma. Through participatory research, mutual cooperation activities have successfully created active engagement between higher education institutions and the community, improved community service, and provided opportunities for community service. Elderly gymnastics has been proven to have a positive impact on the physical health and well-being of the elderly, while Yasin recitations create a spiritual space that supports religious values in the higher education environment.